Radikalisme dan Kaum Muda Dalam Perspektif Sosiologi - Endang Supriadi (Living Islam: Journal of Islamic Discourses, 2018)
Lately radicalism in Indonesia is still warmly discussed. This phenomenon is a serious problem for the community. The organizational network of radicalism does not appear to be conspicuous, but if further examined lately the real threat of radicalism reemerged in Indonesia. This can not be separated from the other side of freedom of democrati- zation. The character or the soul of Indonesia as a nation, often called religus, friendly, tolerant, peaceful, gotong royong, and so on, is now being eroded and experiencing massive degradation. This paper will review the develop- ment of radicalism in Indonesia which in fact young people become agents in the process of the birth of radicalism in the perspective of sociology—the identity of young people as the next generation of the nation is at stake; how far they understand the question of radicalism in Indonesia; and youth radicalism can be seen as a response, criticism and antithesis, to orthodoxy and the mainstream that occurs in power relationships that can take the form of violence and nonviolence.